ANALISIS PUISI ANDUNG SIAN SIRAMBE KARYA CISILIA SIAGIAN: KAJIAN SEMIOTIKA RIFFATERRE - Pardede, Asna Sari; Khairani, Ita (Universitas Batanghari, 2024)
This research aims to (1) describe the analysis of the Andung Sian Sirambe poetry collection by Cisilia Siagian (2) describe the relevance of the meaning of the Andung Sian Sirambe poetry collection by Cisilia Siagian. The data in this research are Toba Batak poetry in an anthology book entitled Andung Sian Sirambe Poetry Collection by Cisilia Siagian, taking 10 works. The instrument in this research is a human instrument, namely researchers who play an important role in the research. This study used descriptive qualitative method. The results of the research obtained in the poem Andung Sian Sirambe by Cisilia Siagian with 10 poems are the change of metaphor meaning in 4 poetry quotes, allegory 1 poetry quote, simile 11 poetry quotes, personification 8 poetry quotes, metonymy 4 poetry quotes, epic parable 2 poetry quotes . Furthermore, there are deviations in meaning, ambiguity consisting of 2 poetry quotes, nonsense, found in 8 poems, contradiction in 2 poetry quotes. Andung Sian Sirambe's poetry collection has the relevant meaning of each poem, such as respect for parents, suffering and difficulties in life, unfair fate, cultural preservation, sacrifice, and life's journey. It is important for readers of the Batak Language Poetry Collection to pay attention to the meaning of the poetry and the language style contained in the poetry in order to be able to understand the picture or essence of the story of the poetry.